[Rezension von: Toth, James, Sayyid Qutb] - Wheatley, Stephanie (A journal of church and state, 2015)
Few Islamist authors have received as much attention in recent years as Sayyid Qutb. Popular portrayals of Qutb paint him as a paranoid, backwards, misogynistic radical. Scholars are more circumspect, and indeed there have been a number of excellent biographies published over the past several years about Qutb. Sadly, the saturated market of Qutb books is perhaps the biggest downfall of James Toth's contribution to the field, Sayyid Qutb: The Life and Legacy of a Radical Islamic Intellectual. Toth presents a balanced, nuanced picture of the often-misunderstood Qutb; however, the ambition of Toth's project ultimately takes away from the final product ...